'The alternative bid'. The failure of Switzerland's candidacy for the 1998 World Cup. (16th November 2020) - Vonnard, Philippe; Berthoud, Jérôme
ABSTRACT: Zero! This is the number of votes Switzerland obtained on 2 July 1992, when the FIFA chose the host country for the 1998 World Cup. Finishing a distant third behind France (12 votes), which was granted the tournament, and Morocco (7 votes) was a massive humiliation for the Swiss Football Association (ASF) and, according to Zurich's influential conservative newspaper Tages Ainzeiger, a national embarrassment. Based on original and various kind of sources, the present paper looks back on Switzerland's failed candidacy in order to identify the motivations underlying the ASF's desire to host the World Cup, the strategies the bid's promoters adopted in response to the challenge posed by the lack of suitable facilities, and the circumstances surrounding the bid's ultimate rejection.